Menelusuri Jejak Sejarah dan Warisan Kultural Kenegerian Lada: Pergulatan Perdagangan Rempah di Pesisir Timur Aceh - Usman; Anis, Madhan; Ibrahim, Husaini; Riyani, Mufti; Rahman, Aulia (Penerbit BRIN (BRIN Publishing), 2024)
Abstract, The Struggle for Spices Trade on the Eastern Coast of Aceh: Tracing the Historical Remain and Cultural Heritage of the Pepper Kingdom. The east coast of Aceh, as part of the Southeast Asian region, has an important role in the history of the spice trade. These trading activities have shaped civilization and international relations for centuries. This research aims to reveal the history of the spice civilization and raise awareness of the historical heritage of spices on the east coast of Aceh. Spices have long been an essential commodity in global trade, influencing the development of civilizations and relations between nations. Nonetheless, over time, knowledge of the important role of the east coast of Aceh in the history of spices is fading. This research uses an interdisciplinary approach that involves historical, archaeological, and ethnographic studies to explore traces of history that are hidden, and scattered on the east coast of Aceh. Through primary data collection, interviews with experts, local researchers, and the local community, as well as direct observation of physical and cultural remains, this research seeks to reconstruct the historical narrative of the heritage of the spice civilization on the east coast of Aceh. This research found that on most of the east coast of Aceh, there are several historical remains related to traces and civilizations of spices in the 17th to 19th centuries. These traces of history are significant in providing information and historical awareness for the people regarding the spice civilization on the east coast of Aceh. It’s just that there are still many challenges to instilling historical awareness about the history of spices. The historical heritage of the spice civilization has not been mapped correctly, and the condition of the heritage that has not been maintained has led to information and narratives on the history of spices on the east coast of Aceh. This research hopes to encourage concrete steps in protecting, preserving, and appreciating the heritage of the pepper kingdom on the East Coast of Aceh for present and future generations. Keywords: Awareness, History, Pepper, Coast, Aceh, Heritage Abstrak, Pesisir timur Aceh, sebagai bagian dari kawasan Asia Tenggara memiliki peran penting dalam jejak sejarah perdagangan rempah. Aktifitas perdagangan tersebut telah membentuk peradaban dan hubungan internasional selama berabad-abad. Penelitian ini bertujuan untuk mengungkap sejarah peradaban rempah dan meningkatkan kesadaran terhadap peninggalan sejarah rempah di pesisir timur Aceh. Rempah telah lama menjadi komoditas penting dalam perdagangan global, mempengaruhi perkembangan peradaban dan hubungan antarbangsa. Meskipun demikian, seiring berjalannya waktu, pengetahuan tentang peran penting pesisir timur Aceh dalam sejarah rempah semakin memudar. Penelitian ini menggunakan pendekatan lintas disiplin ilmu yang melibatkan kajian sejarah, arkeologi, dan etnografi untuk menggali jejak-jejak sejarah yang tersembunyi, bahkan berserakan di pesisir timur Aceh. Melalui pengumpulan data primer, wawancara dengan para ahli, peneliti lokal, dan masyarakat setempat, serta pengamatan langsung terhadap peninggalan-peninggalan fisik dan budaya, penelitian ini berusaha merekonstruksi narasi sejarah peninggalan peradaban rempah di pesisir timur Aceh. Penelitian ini menemukan bahwa di pesisir timur Aceh terdapat beberapa peninggalan sejarah yang berkaitan dengan jejak dan peradaban rempah pada abad ke-17 hingga 19. Jejak peninggalan sejarah tersebut signifikan dalam memberikan informasi dan kesadaran sejarah bagi masyarakat terkait peradaban rempah di pesisir Timur Aceh. Hanya saja, untuk menanamkan kesadaraan sejarah dalam kaitannya sejarah rempah masih ditemui banyak tantangan. Peninggalan sejarah peradaban rempah belum terpetakan dengan baik dan kondisi peninggalan yang tidak terpelihara menyebabkan informasi dan narasi sejarah rempah diwilayah tersebut. Penelitian ini berharap dapat mendorong langkah-langkah konkret dalam menjaga, memelihara, dan menghargai warisan kenegerian lada di pesisir Timur Aceh untuk generasi masa kini dan mendatang. Kata Kunci: Kesadaran, Sejarah, Lada, Pesisir, Aceh, Peninggalan